(untitled) (Dike - Rivista di Storia del Diritto Greco ed Ellenistico, 2015)
A vast enquiry on Greek prose language written in Latin, Guillaume Budé’s Commentarii linguae Graecae (1529, 1548) are also a “thesaurus” of the Greek legal vocabulary that can still be helpful today. Based on the careful study of a large number of Greek quotations, Budé’s Commentarii are conceived like modern dictionaries, except the alphabetical order, which can be obtained thanks to the two Index, Greek and Latin. In fact, Budé’s complex scheme can be reconstructed and corresponds to the evolution of his project. He initially wanted to provide French scholars with a lexicon of legal words that would help the readers with specific meanings found in orators and historians, whom Budé precisely quotes when necessary. The present contribution aims at both showing how to read Budé’s work in its context and giving a comprehensive list of the Greek legal words and expressions which are explained in the first section of Commentarii, with a large number of identified quotations. Vasto studio linguistico della prosa greca redatto in latino, i Commentarii linguae Graecae (1529, 1548) di Guillaume Budé costituiscono altresì un “thesaurus” del lessico giuridico greco che ancor oggi conserva una sua utilità. Fondati sull’esame puntuale di un ampio numero di passi di autori greci, i Commentarii di Budé sono concepiti come i moderni dizionari, ad eccezione dell’ordine alfabetico, che viene comunque fornito attraverso i due indici, greco e latino. Il complesso schema messo in atto da Budé può in effetti essere ricostituito; esso corrisponde all’evoluzione del suo piano di lavoro. Egli volle dapprima offrire agli studiosi francesi un lessico giuridico per aiutarli con i significati specializzati che occorrono nella lettura degli oratori e degli storici, testualmente citati ogni volta che Budé lo ritenne necessario. Il presente contributo intende, da un lato, dare indicazioni per leggere l’opera di Budé nel suo contesto e, dall’altro lato, fornire una lista il più possible comprensiva dei termini e delle espressioni giuridiche spiegate nella prima sezione dei Commentarii, con un largo numero di citazioni identificate.